Effective blood pressure control in arterial hypertension patients: the role of combined fixed-dose pharmaceutical therapy - S. Yu. Martsevich; Yu. V. Lukina; N. S. Oganisyan (Кардиоваскулярная терапия и профилактика, 2006)
Arterial hypertension (AH) is reviewed as the leading cause of cardiovascular disease mortality. The authors stress target blood pressure level achievement as the crucial factor in effective prevention of AH complications. Typically, the latter is possible only with combined pharmaceutical therapy. Information on generic quality is very important for practitioners.